Avalanche dynamics for active matter in heterogeneous media. (7th February 2018) - Reichhardt, C J O; Reichhardt, C
Abstract: Using numerical simulations, we examine the dynamics of run-and-tumble disks moving in a disordered array of fixed obstacles. As a function of increasing active disk density and activity, we find a transition from a completely clogged state to a continuous flowing phase, and in the large activity limit, we observe an intermittent state where the motion occurs in avalanches that are power law distributed in size with an exponent of β = 1.46 . In contrast, in the thermal or low activity limit we find bursts of motion that are not broadly distributed in size. We argue that in the highly active regime, the system reaches a self-jamming state due to the activity-induced self-clustering, and that the intermittent dynamics is similar to that found in the yielding of amorphous solids. Our results show that activity is another route by which particulate systems can be tuned to a nonequilibrium critical state.